Loneliness among college students: examining potential coping strategies and the influence of targeted messages on the likelihood of befriending - Besse, Robin Deshawn (Kansas State University, 2016)
While many different facets of loneliness have been explored, research examining the efficacy of interventions to reduce it has often been overlooked, particularly among college students. Such research is important, as individuals under 25 years of age experience some of the highest rates of loneliness (Victor & Yang, 2012). Furthermore, while the majority of interventions have targeted the lonely individual, few have examined loneliness from the perspective of those around the lonely person. As a result, the objective of the current dissertation was to not only examine the effectiveness of potential interventions in reducing loneliness among college students, but see what types of targeted messages may be successful in increasing helping behavior towards lonely individuals. In Study 1, participants read one of four different types of messages, including mindfulness, changing maladaptive social cognitions, coping behaviors, and control. Although there were no considerable differences in loneliness levels at Time 2 (likely due to participants not being especially lonely), a significant number of individuals reported favoring the mindfulness technique. In Study 2, five different types of targeted messages were utilized, based on Latané and Darley’s (1970) bystander intervention model. These included the "notice" condition, which focused on increasing awareness of lonely others; the "assume responsibility" condition, where responsibility towards helping lonely others was emphasized (as well as awareness); and the "decide (to help)" condition, which offered specific steps to reach out to lonely individuals (in addition to awareness and responsibility); two control conditions were also employed. Results showed that participants in the "decide" condition were significantly more likely to report feeling prepared and inclined to help in the future. In addition, those in the "assume responsibility" and "decide" conditions also reported significantly increased levels of awareness of lonely individuals at the Time 2 follow-up. Together, such results indicate that mindfulness is a technique worth investigating further with regard to reducing loneliness among college students. Furthermore, in order to increase helping behavior, Study 2 suggests that targeting an individual’s specific stage of change may not be necessary; rather, presenting individuals with all relevant information, perhaps at multiple time points, may be particular efficacious.
Keywords: Loneliness